The Impact of Corporate Reputation on Strategies to Increase Consumer Trust - Darman (LifeSciFi, 2024)
Corporate reputation plays a vital role in global marketing, influencing consumer preferences, investor trust, and relationships with business partners. In an increasingly connected digital era, public perception of companies is shaped by a variety of factors, including business ethics, Corporate Social Responsibility (CSR), and operational transparency. This study examines how corporate reputation contributes to the success of global marketing strategies, focusing on the influence of culture on business ethics and innovation in CSR to build a positive image. Using a qualitative approach through literature review, this study highlights that companies with strong reputations tend to be more valued by consumers and have higher competitiveness in international markets. The results of this study provide strategic insights for companies in managing their reputations to achieve business sustainability in a competitive environment.